2018
DOI: 10.1158/1078-0432.ccr-17-3346
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 4 Suppresses Serine/Threonine Kinase 33 Activation and Metastasis of Gastric Cancer through Reversing Epithelial–Mesenchymal Transition

Abstract: Cancers with aberrant expression of Serine/threonine kinase 33 (STK33) has been reported to be particularly aggressive. However, its expression, clinical significance, and biological functions in gastric cancer remain largely unknown. In the present study, we determined the expression and function of STK33 in gastric cancer and delineated the clinical significance of the Krüppel-like factor 4 (KLF4)/STK33 signaling pathway. STK33 expression and its association with multiple clinicopathologic characteristics we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…In addition, decreased KLF4 expression and increased Sp1 expression was a novel molecular mechanism of FOXM1c overexpression and that FOXM1c promoted cancer invasion and metastasis in human pancreatic cancer 19 . Krüppel‐like factor 4 played a negative role in gastric cancer cell invasion, which was reversed by upregulation of serine/threonine kinase 33 expression at the transcriptional level 20 . Our previous studies found that loss of KLF4 expression contributed to enhance human gastric cancer EMT and metastasis development and progression through regulating PODXL 21 .…”
Section: Introductionmentioning
confidence: 98%
“…In addition, decreased KLF4 expression and increased Sp1 expression was a novel molecular mechanism of FOXM1c overexpression and that FOXM1c promoted cancer invasion and metastasis in human pancreatic cancer 19 . Krüppel‐like factor 4 played a negative role in gastric cancer cell invasion, which was reversed by upregulation of serine/threonine kinase 33 expression at the transcriptional level 20 . Our previous studies found that loss of KLF4 expression contributed to enhance human gastric cancer EMT and metastasis development and progression through regulating PODXL 21 .…”
Section: Introductionmentioning
confidence: 98%
“…Gastric cancer (GC) is a major public health problem, ranking the fourth most frequently diagnosed cancer and the second in cancer-associated death worldwide [1]. Although the diagnosis and treatment of GC have been improved, the 5-year overall survival rate of GC remains poor, largely due to diagnostics in advanced stages [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Krüppel‐like transcription factor (KLF4) is a zinger transcription factor and plays a criterial role in regulating cell proliferation, differentiation, apoptosis, and migration . KLF4 has been found to act as an oncogene or tumor suppressor gene in different cancers in a context‐dependent manner .…”
Section: Introductionmentioning
confidence: 99%